Frequency and Clinical Spectrum of Von Willebrand Disease among Females with Bleeding Complaints at TCH-Hyderabad - Sidra Kadir, Noor-Ul-Ain Aziz, Neelam Mazhar, Ikram Din Ujjan, Maleeha, Sadia Kadir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Women with von Willebrand disease experiences more postpartum hemorrhage or the bleeding followed by surgery than the healthy women. Aim: To determine the frequency of Von Willebrand disease among females presenting with bleeding complaints at tertiary care hospital. Study Design: Cross sectional study. Methodology: Complete Blood Count, Bleeding Time, Prothrombin time, Activated Partial Thromboplastin Time were performed on the same day. Blood sample for CBC collected in EDTA tubes and for coagulation assays in tubes containing (3.2%) trisodium citrate. Von Willebrand’s factor: Ag and Factor VIII were analyzed on Sysmex automated blood coagulation analyzer CA (600) while Ristocetin cofactor assay (RiCoF) was performed on Aggregometer. The collected data was analyzed by using SPSS version 25. Chi square ware applied with P-value< 0.05 as significant. Results: Out of 80 patients, 56 patients were unmarried and 24 were married. VWD was found in 22/80 patients (27.5%). Type 3(50%) was the most frequent subtype followed by type2 (22.7%) and type 1(22.7%). In VWD, Menorrhagia (63.6%) was the most frequent symptom. APTT was prolonged in type3 VWD (50%). The mean VWF: Ag 18.5±20, VWF: RICOF 27.7±19 and factor VIII 74.9 ± 62.3 was noted in patients with VWD. Conclusion: It was concluded that VWD is the most common inherited bleeding disorder in females presented with bleeding complaints. Awareness about the disorder is the need of time in order to prevent life threatening bleeding.